(untitled) (Journal of Forest and Livelihood, 2024)
The impact of community forestry program in Nepal is debated around the potentials for empowerment and risk of marginalization. This article draws some evidences of both scenarios. Evidences in the filed show that community forest management process can be a forum for all users including women, poor and ’lower’ castes on the one hand, and equally it can be a vehicle for the elite group of people to legitimize their interests by the unconscious consent of the users, on the other. This articles concludes with a recommendation for monitoring policy implementation and democratizing the Forest User Groups at local level in a way that enables the poor and marginalized to articulate their interests and needs to the decision making process of the forest resource management.